Defining ectosubjectivity: extraction and implantation of protosubjective fragments - Desrochers Ayotte, Alexandre (Sens public)

(untitled) (Département des littératures de langue française, 2020)
This article questions the reterritorialization of human subjectivities by deep learning algorithms and adaptive web platforms, by introducing the concept of ectosubjectivity. This concept, surfacing from a study of the machinic theorizations of Karl Marx and Félix Guattari, attempts to grasp the processual extraction and implantation of subjective fragments by algorithms. The transformative oscillations engendered by these processes are redistributions of human subjectivities towards serialization and mass production. Thus, this article defines ectosubjectivity and questions the transformation of these subjective fragments to fit a homogenized mold.